Modeling Destination Attractiveness: Bagar Hiu's Culinary Tourism Blueprint - Rianty, Rilla; Adawiyah, Robiatul (Indonesian Journal of Tourism and Leisure, 2025)
This study investigates the role of traditional food in cultural tourism development through an examination of Bagar Hiu, a traditional shark-based dish from Bengkulu, Indonesia. The research employs PLS-SEM to analyze survey data collected from 300 tourists, focusing on the relationships between food quality, attractiveness, satisfaction, and behavioral intention. Key findings demonstrate significant direct effects: food quality exhibits strong positive relationships with both attractiveness (p < 0.000) and satisfaction (p < 0.000). Attractiveness significantly influences satisfaction (p < 0.000) and behavioral intention (p < 0.000). Furthermore, satisfaction shows a significant effect on behavioral intention (p < 0.000), while food quality maintains a direct, though weaker, impact on behavioral intention (p = 0.002). These results provide empirical evidence for traditional food's multifaceted role in tourist experiences, particularly highlighting the importance of food attractiveness. The study contributes to culinary tourism literature by quantifying these relationships and identifying satisfaction's mediating role. Practical implications suggest the need for destination managers to emphasize both food quality and presentation while preserving culinary authenticity to enhance tourist satisfaction and behavioral intentions